Peroxisomal Sulfite Oxidase (SOX), an alternative source of NO in higher plants which is upregulated by H2S - Corpas, Francisco J.; Taboada, Jorge; Sánchez-Romera, Beatriz; López-Jaramillo, Javier; Palma, José M. (Plant physiology and biochemistry, 2025)
Nitric oxide (•NO) is a free radical that is endogenously produced in plant cells, though its enzymatic synthesis remains a subject of ongoing debate. Plant peroxisomes, subcellular compartments with active nitro-oxidative metabolism, play a role in various metabolic pathways. Sulfite oxidase (SOX), a peroxisomal enzyme requiring the molybdenum cofactor (MoCo), catalyzes the oxidation of sulfite (SO32−) to sulfate (SO42−), along with the concomitant production of H2O2. Using reconstituted recombinant SOX from pepper (Capsicum annuum L.) fruit, it was shown that this enzyme has the capacity to generate •NO using nitrite (NO2−) as a substrate and NADH as an electron donor which was detected by electron paramagnetic resonance (EPR) spectroscopy coupled with the spin-trapping method. Furthermore, this •NO generation was upregulated in the presence of hydrogen sulfide (H2S) but was downregulated by H2O2 which highlights the relationship between H2O2, •NO, and H2S. This data opens new avenues for understanding the enzymatic sources of •NO in higher plants, particularly within peroxisomes. •Peroxisomal SOX catalyzes the conversion of sulfite to sulfate.•EPR spectroscopy coupled with the spin-trapping is a reliable technique for detecting NO.•Pepper SOX, in the presence of nitrate and NADH, can release NO.•NO generation by SOX in upregulated by H2S but downregulated by H2O2.